Debt Relief with Chinese Characteristics - Deborah Brautigam; Kevin Acker; Yufan Huang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2020)
As China is poised to become the world's largest creditor, concerns about debt sustainability have grown. Yet considerable confusion exists over what is likely to happen when a government runs into trouble repaying its Chinese loans. In this paper, the authors draw on CARI data to review the evidence on China's debt cancellation and restructuring in Africa, in comparative and historical perspective. Cases from Sri Lanka, Iraq, Zimbabwe, Ethiopia, Angola, and the Republic of Congo, among others, point to patterns of debt relief with distinctly Chinese characteristics.
Keywords: 330